Infrastructure for Charging Electric Vehicles’ Effect on Sales in China: Regional Variations and Policy Implications - Chen Yuqi (SHS Web of Conferences)
The market for electric vehicles in China has grown quickly. However, the impact of the quantity and distribution of charging infrastructure on electric vehicle sales has not been thoroughly investigated. This study examines infrastructure for charging electric vehicles’ impact on sales using monthly sales data and charging station data from January 2016 to December 2019. The number of charging stations and sales of electric vehicles have a weak countrywide association, according to regression and correlation analysis. Nevertheless, there is a strong positive association between the quantity of charging stations and the sales of electric vehicles in southern regions like Guangdong and Sichuan, indicating that enhanced charging infrastructure substantially boosts sales. In contrast, in central and northern provinces like Ningxia and Hubei, this effect is more limited, reflecting regional disparities. The study suggests that while improvements in charging infrastructure significantly impact electric vehicle sales in southern regions, other factors such as regional economic development and climate conditions affect northern regions.